An Empirical Evidence of the Impact of Government Tax Revenue on Nigerian Public Debt - Kaka, Emmanuel John (Universitas Syiah Kuala, 2021)
Objective The major objective of this paper is to examine the existence of a mutual consen-sus on the effect of tax revenue and non-tax revenue on public debt in Nigeria.Design/methodology The study uses documentary research design. Data was collect-ed using secondary method of data collection from Debt Management office and Bureau of statistics and Central Bank of Nigeria statistical bulletin data bank. Ordinary Least Square Multi regression model was used in analyzing the dataResults The research found out that there is a negative an insignificant relationship be-tween tax revenue, non-tax revenue and interest rate in relation to Nigerian public debt. Moreover, the paper found out that exchange rate and population rate had significant and positive relationship with Nigerian public debt.Limitation/Suggestion The implication of the study is that, the contribution of tax revenue to the reduction of public debt is minimal as could be shown from the results. While, non-tax revenue contributed more than tax revenue in public debt reduction in Nigeria. In addition, increase in exchange rate, and population rate contributed more to increase in pub-lic debt, while, an increase in interest rate does not increase public debt but rather it discour-ages the government from collecting more debt and push the government to go for other rev-enue sources that where not assessed. The study recommended that; government should harness untapped taxes to increase tax revenue generation to pay interest on loan and princi-pal. Must of the information at the researcher disposal used for the study was for 15 years, from 2003 to 2018. Thus, studies need to be conducted involving more year like from 20 years upward to see whether it will change the result.Novelty/Originality The originality of this research lies on the government inability to generate enough tax revenue and non-tax revenue to meet expenditure without collecting debt. This is because collection of debt always leads to frequent increase in debt burden in Nigeria. Fewer or no one has carried out a careful analysis of the relationship between tax and non-tax revenue against total debt in Nigeria.